2014
DOI: 10.4067/s0717-95022014000200040
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Amelogenin and Lysosome-Associate Membrane Proteins (LAMPs) in Cartilage

Abstract: SUMMARY:Amelogenin is one of the enamel matrix proteins secreted by ameloblasts during enamel formation in tooth development. Recent studies showed that the amelogenin is expressed in chondrocyte. Lysosome-associated membrane proteins (LAMPs) have been identified as binding partner proteins to amelogenin and it has been suggested they act as signaling receptors of amelogenin. The purpose of this study is to clarify the localization of amelogenin and LAMPs in growth plate cartilage and cartilaginous nodules in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Our results showed that several differentiation marker genes in chondrogenic and osteoblast cells were increased by csLRAP and were suppressed in the presence of LAMP-1 antibody. Our previous study suggested that LAMP-1 is involved in chondrogenic differentiation of mesenchymal cells 28) . Thus, our present results suggest that LAMP-1 expression in chondrogenic cells and osteoblast cells is involved in the differentiation process promoted by csLRAP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results showed that several differentiation marker genes in chondrogenic and osteoblast cells were increased by csLRAP and were suppressed in the presence of LAMP-1 antibody. Our previous study suggested that LAMP-1 is involved in chondrogenic differentiation of mesenchymal cells 28) . Thus, our present results suggest that LAMP-1 expression in chondrogenic cells and osteoblast cells is involved in the differentiation process promoted by csLRAP.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, mRNA was reverse-transcribed to cDNA using the iScript TM RT Supermix for RT-qPCR (Bio-Rad, Tokyo, Japan). Real-time PCR was performed using iTaq TM SYBR Green Supermix With ROX (BioRad) for 45 cycles of 95°C for 30 seconds, 60°C for 45 seconds, and 72°C for 30 seconds, using specific primers designed for osteogenic and chondrogenic differentiation marker genes as previously reported 13,[28][29][30] . Mouse Col1a2 specific primers were designed using National Center for Biotechnology Information .…”
Section: Immunofluorescence Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue preparation and immunofluorescence staining were performed according to previously reported methods with minor modifications (Hatakeyama et al, 2014). WT and Amelx* mice (10-week-old) were anesthetized and perfused with 4 % PFA in 0.1M PBS, pH 7.4.…”
Section: Tissue Preparation and Immunofluorescence Stainingmentioning
confidence: 99%
“…), and in the epiphyseal growth plate (Hatakeyama et al. ). Reports suggesting that lysosome‐associated membrane protein 1 (Lamp‐1), a transmembrane protein, serves as a cell surface binding receptor for full length amelogenin and leucine‐rich amelogenin peptide (LRAP), a small amelogenin gene‐spliced product, indicate a possibility that amelogenin may function as a paracrine or autocrine molecule in cell signaling (Tompkins et al.…”
Section: Introductionmentioning
confidence: 99%